Iqra' As the Beginning of Civilization Transformation Thematic Interpretation of QS. Al Alaq Verses 1-5 - Avicena, Fayiz Yan; Azizah, Alfiyatul (Universitas Muhammadiyah Surakarta, 2024)
Surah Al-'Alaq verses 1-5, the first revelation to Prophet Muhammad SAW, underscores the foundational command to